Genotyping of bacteria isolated from clinical sources using (GTG)5-PCR and TP-RAPD - Mohammed Ahmed Bazia Sawynan; Zeina Sabry Muslim Mohammed; Haneen Zaman Khudair Omran Kashkul; Noor Mohammed Ahmed Mohammed; Saja Turkie Majeed Annag (Genius Journals, 2024)
This study was conducted in the Molecular Biology Laboratory and the Central Laboratory - Tikrit University for a period of time with the aim of molecular characterization of Salmonella bacteria from 120 stool samples taken from children suffering from diarrhea, aged 1-60 months in the city of Tikrit, Iraq. DNA was extracted from samples previously diagnosed at the genus level based on the morphological characteristics of the colonies and biochemical tests. The diagnosis of bacterial isolates was also confirmed using the Vitek2 compact system. The results showed the diagnosis of nine strains belonging to the type Salmonella enterica subsp. enterica GTG5 and TP RAPD PCR indicators, the presence of linkage regions and bands in all types of studies in a different manner, and thus it is possible to have closeness and genetic distance between the study samples according to the regions targeted in each indicator
Keywords: Clinical Sources; Salmonella Enterica